2020
DOI: 10.3390/molecules25082004
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Kavalactone Analogues with Increased Potency and Selective Anthelmintic Activity against Larvae of Haemonchus contortus In Vitro

Abstract: Kava extract, an aqueous rhizome emulsion of the plant Piper methysticum, has been used for centuries by Pacific Islanders as a ceremonial beverage, and has been sold as an anxiolytic agent for some decades. Kavalactones are a major constituent of kava extract. In a previous investigation, we had identified three kavalactones that inhibit larval development of Haemonchus contortus in an in vitro-bioassay. In the present study, we synthesized two kavalactones, desmethoxyyangonin and yangonin, as well as 17 anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…108 An SAR investigation identified a superior synthetic analogue WEHI-408 ( 3.93 ) (IC 50 0.59 μg mL −1 ) with no cytotoxicity against HepG2 cells (IC 50 > 40 μg mL −1 ). 109 The previous study also reported goniothalamin ( 3.94 ) from the commercial hardwood tree Cryptocarya novoguineensis (Lauraceae) as active (arguably inactive!) against H. contortus L4 larval development (IC 50 1000 μg mL −1 ), but with more promising activity against H. contortus L4 motility (IC 50 40–60 μg mL −1 ).…”
Section: Plantsmentioning
confidence: 93%
See 1 more Smart Citation
“…108 An SAR investigation identified a superior synthetic analogue WEHI-408 ( 3.93 ) (IC 50 0.59 μg mL −1 ) with no cytotoxicity against HepG2 cells (IC 50 > 40 μg mL −1 ). 109 The previous study also reported goniothalamin ( 3.94 ) from the commercial hardwood tree Cryptocarya novoguineensis (Lauraceae) as active (arguably inactive!) against H. contortus L4 larval development (IC 50 1000 μg mL −1 ), but with more promising activity against H. contortus L4 motility (IC 50 40–60 μg mL −1 ).…”
Section: Plantsmentioning
confidence: 93%
“…108 Notwithstanding these observations, it should be noted that 3.94 is known to be cytotoxic. 109,110 The Bhutanese medicinal plant Pleurospermum amabile (Apiaceae) which is traditionally used as a cleansing and detoxication agent produces bergapten (3.95) and isomyristicin (3.96). 111 Application of the xWORM 112 technique and SEM-based imaging on T. muris established activity for 3.95 (IC 50 11 mg mL −1 ) and 3.96 (IC 50 21 mg mL −1 ), 113 with 3.95 (IC 50 100 mg mL −1 ) and 3.96 (IC 50 150 mg mL −1 ) also showing activity against the human water-borne parasite Schistosoma mansoni.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Four of synthesized analogs showed activities far greater than either of the parent compounds. All the synthesized compounds including the original kavalactones did not show toxicity against human HepG2 hepatoma cells in vitro with the most potent derivative showing the most selectivity [59]. A diverse set of natural compounds with prodigious potential to drug discovery is marine compounds.…”
Section: Natural Productsmentioning
confidence: 99%
“…Kavalactone Analogues. Lately, it was explored that kavalactone analogues exhibited in vitro anthelmintic activities against Haemonchus contortus larvae [75]. rough the chemical modifications of 2-,3-, and 4-substituent on the pendant aryl ring (Figure 7), two kavalactones (yangonin and desmethoxyyangonin) and 17 analogues were synthesized.…”
Section: Antifibrotic and Antioxidant Propertiesmentioning
confidence: 99%
“…Through the chemical modifications of 2- ,3-, and 4-substituent on the pendant aryl ring ( Figure 7 ), two kavalactones (yangonin and desmethoxyyangonin) and 17 analogues were synthesized. Among these analogues, compounds with 4-trifluoromethoxy, 4-phenoxy, 4-difluoromethoxy, and 4-N-morpholine substitutions showed convinced anthelmintic activities (1.9 μ M < IC 50 < 8.9 μ M) which were superior to desmethoxyyangonin (IC 50 = 37.1 μ M) and yangonin (IC 50 = 15.0 μ M) and, thus, provided an opportunity for developing novel anthelmintic agents [ 75 ].…”
Section: The Investigation Of the Structure-activity Relationship (Sar)mentioning
confidence: 99%